Low mass pseudoscalar dark matter in an extended B - L model - Fortes, E. C.F.S. [UNESP]; Tonasse, M. D. [UNESP] (American Physical Society (APS), 2014)
We study an extended B-L model, which has in its structure four neutral scalars. In this model, a representative set of parameters enable us to conclude that one of these scalars is a promising candidate for low-mass dark matter. We introduce a Z2 symmetry, which ensures the stability of the dark matter. The dominant annihilation process will be through the s channel of the Scalar boson exchange in bb̄. So, this is also a Higgs-portal dark matter model, but the Higgs decay to dark matter is suppressed and meets the constraints from invisible decays of the Higgs boson. The model is also in agreement with the constraints established by the XENON100, CoGeNT, and CDMS experiments, matching the relic abundance and the cross section with the nucleon. © 2014 American Physical Society.